Liberalism and democracy in Carlos Lacerda (Ágora Journal, 2023)
The purpose of this article is to investigate how Carlos Lacerda appropriated discussions promoted in the context of the 1930 revolution regarding culture and politics in Brazil. More specifically, it is necessary to ask how the journalist interpreted the relationship between liberalism and democracy, in view of the space of experience demarcated by the 1937 dictatorship and the horizon of expectation offered by the “democracy of the elites”. To answer this question, I will discuss the relationship between liberalism and democracy, followed by comments on the work of Oliveira Vianna, Azevedo Amaral and Francisco Campos. Finally, I will analyze articles published by Carlos Lacerda in the Tribuna da Imprensa, between 1950 and 1955, a period that includes the second Getúlio Vargas government, two presidential elections and several questions about democratic institutions.